Bimetallic Aluminum‐ and Niobium‐Doped MCM‐41 for Efficient Conversion of Biomass‐Derived 2‐Methyltetrahydrofuran to Pentadienes. (17th November 2022) - Fan, Mengtian; Xu, Shaojun; An, Bing; Sheveleva, Alena M.; Betts, Alexander; Hurd, Joseph; Zhu, Zhaodong; He, Meng; Iuga, Dinu; Lin, Longfei; Kang, Xinchen; Parlett, Christopher M. A.; et al.
Abstract: The production of conjugated C4–C5 dienes from biomass can enable the sustainable synthesis of many important polymers and liquid fuels. Here, we report the first example of bimetallic (Nb, Al)‐atomically doped mesoporous silica, denoted as AlNb‐MCM‐41, which affords quantitative conversion of 2‐methyltetrahydrofuran (2‐MTHF) to pentadienes with a high selectivity of 91 %. The incorporation of Al III and Nb V sites into the framework of AlNb‐MCM‐41 has effectively tuned the nature and distribution of Lewis and Brønsted acid sites within the structure. Operando X‐ray absorption, diffuse reflectance infrared and solid‐state NMR spectroscopy collectively reveal the molecular mechanism of the conversion of adsorbed 2‐MTHF over AlNb‐MCM‐41. Specifically, the atomically‐dispersed Nb V sites play an important role in binding 2‐MTHF to drive the conversion. Overall, this study highlights the potential of hetero‐atomic mesoporous solids for the manufacture of renewable materials. Abstract : The highly selective conversion of biomass‐derived 2‐methyltetrahydrofuran (2‐MTHF) into pentadienes has been achieved over an aluminum and niobium bimetallic atomically doped MCM‐41. The Nb V sites enhance the catalytic performance by binding 2‐MTHF.